Possibilities of forms and types of extra-curricular research activity in the formation of students’ creative competences of technical higher educational establishments - Vostroknutov, Evgen Volodymyrovych (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
<!– [if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Introduction. In modern society the special actuality by the problem of upgrading the quality of students’ training of technical higher educational establishment by the formation of their creative competence is acquired. Nowadays interest for society and employer at the market of labour presents graduating student of technical higher educational establishment, aimed at the search of new, eccentric decisions of technical tasks with formed creative style of professional thought. under research activity the author understands: fundamental (theoretical, experimental) scientific researches, directed on the receipt of new knowledge; applied scientific researches, directed on application of new knowledge; experimental developments on the base of knowledge, purchased as a result of leadthrough of scientific researches; creation of new materials, products, methods and its further perfection. Purpose. To show possibilities of forms and types of extra-curricular research activity in the formation of students’ creative competences of technical higher educational establishments. Methods. Theoretical and empirical methods of scientific and pedagogical study are used. Results. On the basis of theoretical analysis it was exposed that all those elements are revealed in the structure of research activity, that there are elements of creative activity: reason is an aggregate of the socially conditioned and personality necessities, which is directed on the subject research; purpose – is a receipt of objective new knowledge about reality; object – selected for the study of reality; subject is an aggregate of the set properties of object; process is a sequence of executions, flowing in accordance with logic of scientific research; product – is an objectively new knowledge about reality. Research activity is one of numerous forms of creative activity. Consequently, research activity is an instrument in formation and development of creative competence. Intercommunication of research and creative activity is represented. Description of students’ research activity types is given: educational-research and extra-curricular research activity. The forms of students’ extra-curricular research activity of technical higher educational establishments are determined: scientific conferences; scientific forums, competitions; exhibitions of scientific and technical creation of youth; students’ scientific society, design office; temporal creative groups; research works; competitions of grants. The accordance of organizational forms and matter of students’ extra-curricular research activity of technical higher educational establishment is represented. A conclusion about estimating the level of formation of motivational, cognitive and action-practical components of creative competence of technical higher educational establishment students’ is formulated. Originality. On the basis of products of students’ extra-curricular research activity of technical higher educational establishments it is possible to estimate formed of action-practical components of creative competence of technical higher educational establishment students’. Conclusion. The presence of the developed products of students’ extra-curricular research activity supports positive motivation for students to carrying on scientific activity, that straight determines the level of formed of motivational component of creative competence of technical higher educational establishment students’. Perspective is that extra-curricular research activity provides formation of students’ creative competence that will be confirmed in our further researches. <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>